Trajectory and spacecraft design for a pole-sitter mission - Ceriotti, Matteo; Heiligers, Jeannette; McInnes, Colin (Journal of Spacecraft and Rockets, 2014)
This paper provides a detailed mission analysis and systems design of a pole-sitter mission. It considers a spacecraft that is continuously above either the North or South Pole and, as such, can provide real-time, continuous and hemispherical coverage of the polar regions. Two different propulsion strategies are proposed, which result in a near-term pole-sitter mission using solar electric propulsion and a far-term pole-sitter mission where the electric thruster is hybridized with a solar sail. For both propulsion strategies, minimum propellant pole-sitter orbits are designed. Optimal transfers from Earth to the pole-sitter are designed assuming Soyuz and Ariane 5 launch options, and a controller is shown to be able to maintain the trajectory under unexpected conditions such as injection errors. A detailed mass budget analysis allows for a trade-off between mission lifetime and payload mass capacity, and candidate payloads for a range of applications are investigated. It results that a payload of about 100 kg can operate for approximately 4 years with the solar-electric spacecraft, while the hybrid propulsion technology enables extending the missions up to 7 years. Transfers between north and south pole-sitter orbits are also considered to observe either pole when illuminated by the Sun.